English (Brazilian Journal of Pharmaceutical Sciences, 2023)
Testicular damage is one of the most hazardous effects of chemotherapy as it is frequently associated with oligozoospermia and azoospermia. This study aimed at evaluating the protective effect of melatonin in a rat model of busulfan-induced testicular injury. Rats were divided into four groups: control, melatonin, busulfan, busulfan plus melatonin. After 15 days, the semen was collected from the epididymis and testes were assessed. Sperm removed from cauda epididymis and analyzed for sperm count and viability. Testis tissues were also removed, fixed in formalin and were embedded in paraffin. Sections of testis tissue were stained with hematoxylin-eosin for histological examination and prepared for TUNEL (Terminal deoxynucleotide transferase dUTP Nick End Labeling) assay to detect apoptosis and PCNA (proliferating cell nuclear antigenassay) to detect proliferation cells. Serum and testes supernatants were separated to detect testosteron level and oxidative stress parameters. In histological examination, degenerative changes in seminiferous tubules were observed in the experimental groups. In biochemical examination, the total oxidant status (TOS) levels in Busulfan group were significantly higher than in the control group while the total antioxidant status (TAS) levels of all the groups were similar. In conclusion, the beneficial properties of melatonin treatment by its potent anti-oxidants may reduce adverse effects of chemotherapy in the reproductive system in a rodent system